The impact of the war in Ukraine on the perinatal period: Perinatal mental health for refugee women (pmh-rw) protocol - Rodríguez-Muñoz, Maria F.; Chrzan-Dętkoś, Magdalena; Uka, Ana; García-López, Helena S.; Krupelnytska, Liudmyla; Morozova-Larina, Olha; Vavilova, Alona; Molotokas, Antonina; Murawska, Natalia; Le, Huynh-Nhu (Frontiers in Psychology, 2023)
Background: The aim of the Perinatal Mental Health for Refugee Women (PMH-RW) Project is to investigate the impact of the war on perinatal mental health: depression, anxiety, post-traumatic stress, and birth trauma symptoms. This project will also assess the protective factors (such as personality traits, social support, sociodemographic characteristics, and access to medical/mental health services). Method: An international observational cohort study with baseline data is being assessed in Ukraine (for internal refugees) and several European Countries (for external refugees). - The sample consists of pregnant and postpartum women (with infants up to 12 months of age). The assessment includes measures on depression (EPDS), anxiety (GAD-7), experiences during birth (City Birth Questionnaire), post-traumatic stress symptoms (Impact of events scale – revised (PTSD-R), Personality (Ten-Item Personality Inventory-TIPI), and a questionnaire for socio-demographic data which also such social support. Conclusions: This study will provide needed information for understanding the impact of the Ukrainian Crisis on perinatal mental health by studying potential risk and protective factors. The findings will help policymakers develop tailored mental health prevention strategies or interventions for perinatal refugees. Trial registration: ClinicalTrials.gov Identifier: NCT05654987